Pemberdayaan Petani Alpukat Desa Tuwiri Kulon Kabupaten Tuban Melalui Penyuluhan Digital Marketing Dalam Upaya Akselerasi Perekonomian Desa - witri krisdayanti; Kusumawati, Nunik Dwi; Akbar, Rasyidi Faiz (Abimanyu : Jornal of Community Engagement, 2022)
The implementation of community service in an effort to fulfill the obligations of the Tri Dharma of Higher Education by KKNT-MBKM Unesa Tuban 3 in 2022 was carried out in Tuwiri Kulon Village, Merakurak District, Tuban Regency, one of which was focused on empowering avocado farmers in digital marketing counseling. Avocado is one of the plantation commodities in Tuwiri Kulon Village which is the prima donna of local fruit sold in foreign markets. The ability of the community to manage avocado plantation products that have export value will have an impact on accelerating the village economy. Based on the above, digital marketing counseling is an effort to prepare and adjust the skills of avocado farmers with technological advances in welcoming the distribution and expansion of avocado marketing so that it has an impact on the welfare of the village economy. The method used in this community service is in the form of public education in counseling on digital marketing understanding and technical avocado marketing strategies by a professional web Facebook Ads. The results of community service obtained are expanding knowledge and learning experiences of students outside campus and increasing awareness and productivity of PKM objects in the use of digital marketing platforms to create competitive opportunities in marketing agricultural and plantation products. Participants showed considerable interest in continuously marketing their products through social media in the future.